Pengaruh Budaya Kerja terhadap Kinerja Guru SD IT An-Nuriyah Sekayu - Oktarina, Mely; Purnamasari, Endah Dewi; Handayani, Susi (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to analyze the effect of work culture on the performance of teachers at SD IT An-Nuriyah Sekayu. This study used primary data and secondary data. Data collection techniques are carried out by observing and distributing questionnaires to all members of 25 respondents. The research method applied in this research is simple linear regression analysis. The results indicates that work culture (X) had a significant positive effect on performance (Y). This research is useful for improving performance through workculture